Chiari Type I Malformation - J Gordon Millichap (Pediatric Neurology Briefs Publishers, 1988)
A 13-year-old girl with post-traumatic cerebellar ataxia, transient upper extremity weakness, and lower cranial nerve dysfunction was found to have a Type I Chiari malformation on MRI at the Depts of Neurosurgery and Neurology, San Francisco General Hospital, California.